Intra-arterial Thrombectomy with Stent Retriever for Acute Ischemic Stroke – a Retrospective, Single-centered Study from Brazil - Gatto, Luana Antunes Maranha; Zétola, Viviane de Hiroki F.; Demartini Junior, Zeferino; Nascimento, Fábio A.; Koppe, Gelson Luis (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Objective To report our initial experience with intra-arterial thrombectomy (IAT) with stent retriever for acute ischemic stroke.Methods We conducted a retrospective review of patients with acute ischemic stroke who underwent IAT from September 2010 to August 2016.Results Forty-one patients were included; mean age was 57 years (range: 29–85), and 54% were women. There were 32 anterior circulation occlusions, and 11 posterior circulation occlusions. The mean value of the National Institutes of Health Stroke Scale (NIHSS) upon admission (available in 9/41 patients) was 14 (range: 6–20). Nineteen patients had favorable outcomes (modified Rankin Scale [mRS]: 0–2 at 6 months), and 22 had unfavorable outcomes (mRS: 3–6 at 6 months). The mortality rate was 37% (15/41). Favorable outcomes were associated with revascularization within the first 360 minutes of the onset of symptoms (p = 0.000001), and satisfactory revascularization (thrombolysis in cerebral infarction [TICI] scale: 2b or 3) (p = 0.0018).Conclusion It is of paramount importance to educate stroke teams on the benefits of IAT for acute ischemic stroke and the population on identifying stroke and seeking immediate care following symptom onset.
Keywords: endovascular treatment; intra-arterial thrombectomy; mechanical thrombectomy; ischemic stroke